SATU INJIL BAGI SEGALA BUDAYA - Cornelis J. Haak (Phronesis: Jurnal Teologi dan Misi, 2021)
This article explains the need the development of Reformed theology so that it can attract the attention of different cultured people with Guilt Culture. It turns out the gospel applies to all cultures, but theology of Reformed raises Luther's question that is looking for an answer about the basis of salvation. Even though it strongly agreed that the Bible was teaching that it was dismissed by justification through faith, but the recognition of 'Sola Fide' did not contain the overall gospel. Therefore, the meaning and impact of the gospel should be presented to a shame culture and a fear culture (Fear Culture) in more suitable to the questions and struggle that contexts. if characteristic every culture is more regularly understood, it can also read the Bible and the teachings of the gospel with 'lens' which are more in line with those cultural needs. With this the good news of the Gospel will get stronger to convince the listeners of the gospel.